Off the beat: my life as a brown, Muslim woman in the Met - Mehtab, Nusrit (Torva, 2024)
When Nusrit Mehtab joined the Met Police in the late 80s the organisation was rife with racism and misogyny. Officers refused to patrol with her, or even call her by her name. Her attempts to get promoted were met with hostility and ridicule and she was subject to cruel pranks. As the years passed and her seniority grew, Nusrit was dismayed to find that these problems got worse, not better. After 30 years, she finally had enough and left the Met, initiating an employment tribunal against them in the process. Now lecturing new recruits in policing law and criminology, she's confident that we can mould the next generation of officers to create a more inclusive police force, safer for both the officers and the public